On Pointwise Deferred Statistical Convergence of Sequences of Fuzzy Mappings - Sengul, Hacer; Et, Mikail (Amer Inst Physics, 2019)
In this study, we introduce the concepts of pointwise deferred statistical convergence and strongly deferred Cesaro pointwise summable sequences of fuzzy mappings. Some relations between pointwise deferred statistical convergence and strongly deferred Cesaro pointwise summable sequences of fuzzy mappings are given.
International Conference of Mathematical Sciences (ICMS) -- JUL 31-AUG 06, 2018 -- Maltepe Univ, Istanbul, TURKEY
Keywords: Sequences; series; summability; functional analysis